Amyloid‐Like Fibrillary Morphology Originated by Tyrosine‐Containing Aromatic Hexapeptides. Issue 26 (26th April 2018) - Diaferia, Carlo; Balasco, Nicole; Sibillano, Teresa; Ghosh, Moumita; Adler‐Abramovich, Lihi; Giannini, Cinzia; Vitagliano, Luigi; Morelli, Giancarlo; Accardo, Antonella
Abstract: Phenylalanine‐based nanostructures have attracted the attention of the material science community for their functional properties. These properties strongly depend on the hierarchic organization of the nanostructure that in turn can be finely tuned by punctual chemical modifications of the building blocks. Herein, we investigate how the partial or the complete replacement of the Phe residues in PEG8 ‐(Phe)6 (PEG8 ‐F6) with tyrosines to generate PEG8 ‐(Phe‐Tyr)3 (PEG8 ‐(FY)3) or PEG8 ‐(Tyr)6 (PEG8 ‐Y6) affects the structural/functional properties of the nanomaterial formed by the parental compound. Moreover, the effect of the PEG derivatization was evaluated through the characterization of the peptides without the PEG moiety (Tyr)6 (Y6) and (Phe‐Tyr)3 ((FY)3). Both PEG8 ‐Y6 and PEG8 ‐(FY)3 can self‐assemble in water at micromolar concentrations in β‐sheet‐rich nanostructures. However, WAXS diffraction patterns of these compounds present significant differences. PEG8 ‐(FY)3 shows a 2D WAXS oriented fiber diffraction profile characterized by the concomitant presence of a 4.7 Å meridional and a 12.5 Å equatorial reflection that are generally associated with cross‐β structure. On the other hand, the pattern of PEG8 ‐Y6 is characterized by the presence of circles typically observed in the presence of PEG crystallization. Molecular modeling and dynamics provide an atomic structural model of the peptide spine of these compounds that is in good agreement with WAXS experimental data. Gelation phenomenon was only detected for PEG8 ‐(FY)3 above a concentration of 1.0 wt % as confirmed by storage ( G ′≈100 Pa) and loss ( G ′′≈28 Pa) moduli in rheological studies. The cell viability on CHO cells of this soft hydrogel was certified to be 90 % after 24 hours of incubation. Abstract : Nanobiology : The partial or complete replacement of the Phe residue with a Tyr one in ancestor PEG8 ‐F6 alters the structure of the self‐assembled material from fibers to soft hydrogels with a high in vitro biocompatibility.